KEANEKARAGAMAN JENIS SATWALIAR DI KAWASAN PERKEBUNAN KELAPASAWITDAN STATUS PERLINDUNGANNYA: STUDI KASUS DI KAWASAN UNIT PENGELOLAAN PT. TANDAN SAWITA PAPUA, KABUPATEN KEEROM, PAPUA - Harnios Arief (Department of Forest Resources Conservation and Ecotourism - IPB University, 2012)
Forests development into oil palm plantations of course have much impact on the environment within and surrounding both direct and indirect impacts. One of the affected is wildlife. Based on field observations during the course of the study, it is known there are 19 species of mammals, 47 species of birds and 5 species of reptiles. Based on the analysis, this region contains of 10 species of mammals, 16 species of birds and 4 species of reptiles which includes the category of rare / protected. Poaching, habitat destruction, the unclear status of the land, and the decline in feed quality is a serious threat to the existence of wildlife in the region. Keywords: ecosystems, habitats, wildlife, and wildlife species diversity.